Plebopus portentosus polysaccharide nano-silver hydrogel as well as preparation method and application thereof
By adjusting the ratio of polyvinyl alcohol, gelatin and carboxymethyl chitosan, combined with redox reaction and physical crosslinking, a dark brown vein stalker polysaccharide nanosilver hydrogel with stable parameter performance was prepared, and the solution was solved The problem of fuzzy preparation process parameters in the prior art has achieved effective inhibition of E. coli and Staphylococcus aureus, and has good biocompatibility and drug release performance.
Patent Information
- Application Number
- CN202411195506.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the preparation process parameters of the polysaccharide nanosilver hydrogel of Dark Brown Vein Porcini Porcini are blurred, resulting in unstable antibacterial effect.
By adjusting the ratio of polyvinyl alcohol, gelatin and carboxymethyl chitosan, combined with redox reaction and physical crosslinking, a dark brown vein stalker polysaccharide nanosilver hydrogel with stable parameter performance was prepared. The specific process The parameters are the ratio of polysaccharides of dark brown vein stalk: silver nitrate: hydrogel raw materials: 0.2mg/mL: 0.004mmol/mL: 0.17~0.32g/mL, polyvinyl alcohol, gelatin and carboxymethyl chitosan The mass ratio is 1:1 to 2:1 to 2, the reaction temperature is 50°C, the reaction time is 90 minutes, the mass fraction of the hydrogel raw material is 27%, and the mass ratio of the raw material is 1:1:1.
The prepared dark brown vein styrofolia polysaccharide nanosilver hydrogel has a swelling rate of 571%, a 65% water loss rate and a 27% degradation rate, which can effectively inhibit the growth of E. coli and Staphylococcus aureus, and is equipped with Good adhesion and ductility.
Smart Images

Figure CN119258006A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite hydrogel materials, and in particular relates to a Boletus edulis polysaccharide nanosilver hydrogel and a preparation method and application thereof. Background Art
[0002] Phlebopus portentosus, also known as Phlebopus portentosus or Phlebopus edulis, has a fruiting body rich in polysaccharides, which are its main functional active ingredients and have multiple biological activities such as anti-oxidation, antibacterial, anti-tumor, hypoglycemic, hypotensive, hypolipidemic and neuronal cell protection.
[0003] Silver nanoparticles (AgNPs) can kill bacteria by slowly releasing silver ions and producing reactive oxygen species (ROS) due to their special structure and physicochemical properties. Silver nanoparticles have unique chemical stability, thermal stability and antibacterial activity, but their particle size distribution is wide and they are prone to agglomeration, so stabilizers need to be added to prevent agglomeration.
[0004] Hydrogel is a polymer material with a three-dimensional network structure, showing good biocompatibility, drug loading and sustained release properties, and has a unique porous structure, permeability and hydrophilicity. As a wound repair dressing, hydrogel has strong water retention and adhesion, and can provide effective isolation, moisture and drug release for the wound.
[0005] The preparation methods of nanosilver hydrogel mainly include in-situ reduction method, co-polymerization method and physical cross-linking method. The in-situ reduction method utilizes the complexation and adsorption effect of the unique functional groups in the modified hydrogel on metal ions, and the steric hindrance generated by the network structure of the hydrogel stabilizes and confines the nano-metal particles, effectively preventing the agglomeration of nano-metal particles. The co-polymerization method is to mix the prepared nano-metal particles with monomers, and embed the nano-metal particles into the spatial network structure of the hydrogel through polymerization reaction to obtain nano-metal composite hydrogel. The physical cross-linking method is also called the freeze-thaw method. Nanosilver hydrogel has excellent antibacterial effect, adhesion and water absorption properties, so it has attracted much attention in the medical field.
[0006] However, the current research on the preparation process of Boletus edulis polysaccharide nanosilver hydrogel is still relatively limited. Summary of the invention
[0007] In order to overcome the problem of fuzzy preparation process parameters of Boletus edulis polysaccharide nanosilver hydrogel, the present invention proposes specific preparation process parameters, which can prepare Boletus edulis polysaccharide nanosilver hydrogel with antibacterial effect.
[0008] On the one hand, the present invention relates to a dark brown stalked boletus polysaccharide nanosilver hydrogel, comprising dark brown stalked boletus polysaccharide, silver nitrate and hydrogel raw materials, with a ratio of 0.2 mg / mL: 0.004 mmol / mL: 0.17-0.32 g / mL.
[0009] Furthermore, the hydrogel raw materials include polyvinyl alcohol (PVA), gelatin and carboxymethyl chitosan (CMCS) in a mass ratio of 1:1-2:1-2.
[0010] Furthermore, the ratio of dark brown-veined boletus polysaccharide, silver nitrate and hydrogel raw material was 0.2 mg / mL:0.004 mmol / L:0.27 g / mL, the mass ratio of polyvinyl alcohol, gelatin and carboxymethyl chitosan was 1:1:1, and the swelling rate, water loss rate and degradation rate of dark brown-veined boletus polysaccharide nanosilver hydrogel were 571%, 65% and 27%, respectively.
[0011] Furthermore, the dark brown veined boletus polysaccharide nanosilver hydrogel can inhibit the growth of Escherichia coli and Staphylococcus aureus.
[0012] In another aspect, the present invention relates to a method for preparing the above-mentioned Suillus edulis polysaccharide nanosilver hydrogel, comprising:
[0013] Adding the dark brown veined boletus polysaccharide solution to the silver nitrate solution, reacting for 120 minutes in the dark at 90° C. and 120 r / min, to obtain the dark brown veined boletus polysaccharide nanosilver solution;
[0014] Polyvinyl alcohol was added to the dark brown-veined boletus polysaccharide nanosilver solution, dissolved at 90°C, cooled to 50°C, gelatin was added, and carboxymethyl chitosan was added after dissolution, and reacted at 30-60°C for 15-60 minutes to obtain the dark brown-veined boletus polysaccharide nanosilver hydrogel.
[0015] Furthermore, polyvinyl alcohol, gelatin and carboxymethyl chitosan were added to the dark brown vein boletus polysaccharide nanosilver solution, and the mixture was reacted at 50° C. for 30 minutes to obtain the dark brown vein boletus polysaccharide nanosilver hydrogel.
[0016] On the other hand, the present invention relates to the use of the above-mentioned Suillus edulis polysaccharide nanosilver hydrogel in the preparation of a preparation for inhibiting or killing Escherichia coli and / or Staphylococcus aureus.
[0017] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects or advantages:
[0018] The present application successfully prepared dark brown vein boletus polysaccharide by water extraction and alcohol precipitation method, and subjected it to redox reaction with silver nitrate to synthesize dark brown vein boletus polysaccharide nanosilver complex. By adjusting the ratio of polyvinyl alcohol, gelatin and carboxymethyl chitosan in the hydrogel raw materials, dark brown vein boletus polysaccharide nanosilver hydrogel with stable parameter performance was prepared. The structural characterization of dark brown vein boletus polysaccharide nanosilver hydrogel showed that it had a porous structure inside and a high cross-linking density, which was conducive to oxygen supply, drug release and absorption of exudate. Through single factor experiments and response surface optimization, the optimal process conditions for preparing dark brown vein boletus polysaccharide nanosilver hydrogel were determined as follows: reaction temperature 50℃, reaction time 90min, hydrogel raw material mass fraction 27%, and raw material mass ratio 1:1:1. Under these conditions, the swelling rate, water loss rate and degradation rate of the prepared polysaccharide nanosilver complex hydrogel were 571%, 65% and 27%, respectively, with good adhesion and ductility. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can still be obtained based on these drawings without creative work.
[0020] Figure 1 The effect of reaction temperature on the properties of Suillus edulis polysaccharide nanosilver hydrogel.
[0021] Figure 2 The effect of reaction time on the properties of Suillus edulis polysaccharide nanosilver hydrogel.
[0022] Figure 3 The effect of the mass ratio of hydrogel raw materials on the properties of Suillus edulis polysaccharide nanosilver hydrogel.
[0023] Figure 4 This paper studies the effect of the mass fraction of hydrogel raw materials on the properties of Suillus edulis polysaccharide nanosilver hydrogel.
[0024] Figure 5 This is the response surface diagram of the interactive effects of various factors of dark brown veined boletus polysaccharide nanosilver hydrogel on the comprehensive score. Figure 5 In (a), A is the reaction time, and B is the mass fraction of the hydrogel raw material; Figure 5 In (b), B is the mass fraction of the hydrogel raw material, and C is the mass ratio of the raw materials; Figure 5 In (c), A is the reaction time and C is the mass ratio of raw materials.
[0025] Figure 6This is a diagram showing the adhesion effect of dark brown veined boletus polysaccharide nanosilver hydrogel. Figure 6 (a) shows the dark brown veined boletus polysaccharide nanosilver hydrogel adhered to the back of the hand; Figure 6 (b) shows the dark brown veined boletus polysaccharide nanosilver hydrogel adhered to plastic; Figure 6 (c) shows the dark brown stalked boletus polysaccharide nanosilver hydrogel adhered to the gloves.
[0026] Figure 7 This is the infrared spectrum of Boletus edulis polysaccharide nanosilver hydrogel.
[0027] Figure 8 This is a scanning electron micrograph of the dark brown-veined boletus polysaccharide nanosilver hydrogel.
[0028] Fig. 9 This is a schematic diagram of the inhibition zone of dark brown veined boletus polysaccharide nanosilver hydrogel against Escherichia coli. Fig. 9 (a) is phosphate buffered saline (PBS); Fig. 9 (b) is a dark brown veined boletus polysaccharide nanosilver solution; Fig. 9 (c) is dark brown veined boletus polysaccharide nanosilver hydrogel; Fig. 9 (d) is the blank hydrogel.
[0029] Fig.10 This is a schematic diagram of the inhibition zone of dark brown veined boletus polysaccharide nanosilver hydrogel against Staphylococcus aureus. Fig.10 (a) is phosphate buffered saline (PBS); Fig.10 (b) is a dark brown veined boletus polysaccharide nanosilver solution; Fig.10 (c) is dark brown veined boletus polysaccharide nanosilver hydrogel; Fig.10 (d) is the blank hydrogel. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is described below in conjunction with embodiments; however, the present invention is not limited to the following embodiments.
[0031] The experimental methods and detection methods in the following embodiments are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.
[0032] The dark brown-veined boletus was purchased from the Yunnan Tropical Crops Science Research Institute and was identified as the fruiting body of the dark brown-veined boletus Phlebopus portentosus by Professor Zeng Niankai of Hainan Normal University.
[0033] Example 1
[0034] This example provides a method for preparing Boletus edulis polysaccharide nanosilver hydrogel.
[0035] 1. Preparation of Boletus edulis polysaccharide
[0036] The fruiting bodies of the dark brown-stalked boletus are fully dried and then crushed, passed through a 40-mesh sieve to obtain dark brown-stalked boletus powder, and then packed into a ziplock bag for storage for later use.
[0037] Take 50g of dark brown vein boletus powder, add 1L of 95% ethanol, ultrasonically vibrate for 30min to make the ethanol fully contact with the powder, discard the supernatant, dry, and obtain a precipitate. Add 1L of distilled water to the above precipitate, extract at 80℃ for 80min, centrifuge, filter, collect the filtrate, add 1L of distilled water to the filter residue, extract at 80℃ for 80min, centrifuge, filter, collect the filtrate, repeat this step 3 times, and combine the collected filtrates. The combined filtrate is concentrated under reduced pressure at 60℃. After concentrating to 100mL, slowly add 400mL of 95% ethanol to the concentrate. Stir continuously during the addition of ethanol, make the ethanol and the concentrate fully mixed, then seal it, let it stand at 4℃ for 24h, centrifuge to obtain a precipitate, and freeze-dry the precipitate for 24h to obtain dark brown vein boletus polysaccharide.
[0038] 2. Preparation of Boletus edulis polysaccharide nanosilver solution
[0039] (1) Preparation of Boletus edulis polysaccharide solution: Add 250 mg of Boletus edulis polysaccharide into a beaker, add 50 mL of distilled water, and stir until completely dissolved to obtain a 5 mg / mL Boletus edulis polysaccharide solution. Prepare and use immediately.
[0040] (2) Preparation of silver nitrate solution: Weigh 850 mg of AgNO3 powder, add distilled water to make up to 500 mL, prepare a 10 mmol / L silver nitrate solution, and store in a dark place.
[0041] (3) Preparation of the dark brown veined boletus polysaccharide nanosilver solution: 100 mL of the silver nitrate solution prepared in step (2) is placed in a conical flask, 10 mL of the dark brown veined boletus polysaccharide solution prepared in step (1) is added dropwise, and then 140 mL of ultrapure water is added and shaken thoroughly. The oscillation temperature is set to 90° C. and the oscillation speed is set to 120 r / min. The solution is protected from light and reacted for 120 min.
[0042] 3. Preparation of Boletus edulis polysaccharide nanosilver hydrogel
[0043] Take 30 mL of the dark brown vein boletus polysaccharide nanosilver solution prepared in the above step (3), add 2.7 g of polyvinyl alcohol (PVA), dissolve at 90°C, cool to 50°C, continue to add 2.7 g of gelatin (Gelatin), add 2.7 g of carboxymethyl chitosan (CMCS) after dissolution, and react at 30-70°C for 30 minutes to obtain dark brown vein boletus polysaccharide nanosilver hydrogel (PPP-AgNPs-xP-yG-zC hydrogel, wherein x, y, and z represent the mass ratio of PVA, Gelatin, and CMCS).
[0044] Example 2
[0045] This example provides an experiment on the synthesis process parameters of Boletus edulis polysaccharide nanosilver hydrogel.
[0046] Data analysis and processing method: Each group of experiments was repeated three times, and the data were analyzed using Design-Expert13 software for regression model variance analysis combined with response surface plot analysis.
[0047] 1. Performance test of dark brown stalked boletus polysaccharide nanosilver hydrogel
[0048] 1. Determination of swelling properties
[0049] Cut the dark brown veined boletus polysaccharide nanosilver hydrogel into a size of 1cm×1cm and place it in a 60℃ oven to dry for 24h. After drying, accurately weigh the weight of the dark brown veined boletus polysaccharide nanosilver hydrogel after sufficient drying. Soak the dried dark brown veined boletus polysaccharide nanosilver hydrogel in 25-27℃ distilled water for 24h. Take out the dark brown veined boletus polysaccharide nanosilver hydrogel that has been swollen for 24h, absorb the moisture on the surface, and accurately weigh the weight of the swollen dark brown veined boletus polysaccharide nanosilver hydrogel. Calculate the water absorption rate of PPP-AgNPs hydrogel according to the following formula:
[0050] Water absorption (%) = (M 后 -M 前 ) / M 前 ×100%
[0051] Where M 前 is the weight of the dried Boletus edulis polysaccharide nanosilver hydrogel, M 后 is the weight of the Suillus edulis polysaccharide nanosilver hydrogel after swelling for 24 hours.
[0052] 2. Water loss performance test
[0053] Cut the dark brown veined boletus polysaccharide nanosilver hydrogel into a size of 1cm×1cm and weigh it accurately. Then, place it at 25-27℃ for 24h, and weigh the dark brown veined boletus polysaccharide nanosilver hydrogel accurately again. Calculate the water loss rate of the dark brown veined boletus polysaccharide nanosilver hydrogel according to the following formula:
[0054] Water loss rate (%) = (M 前 -M 后 ) / M 前 ×100%
[0055] Where M 前 is the weight of the initial cut Boletus edulis polysaccharide nanosilver hydrogel, M 后 It is the weight of the dark brown veined boletus polysaccharide nanosilver hydrogel after standing at 25-27°C for 24 hours.
[0056] 3. Degradation performance test
[0057] Cut the dark brown vein boletus polysaccharide nanosilver hydrogel into a size of 1cm×1cm, place it in a 60℃ oven to dry for 24h, and accurately weigh the weight of the dark brown vein boletus polysaccharide nanosilver hydrogel after sufficient drying. Soak the dried dark brown vein boletus polysaccharide nanosilver hydrogel in distilled water for 24h. Take out the dark brown vein boletus polysaccharide nanosilver hydrogel that has swollen for 24h, absorb the water on its surface, and then place it in a 60℃ oven to dry for 24h again, and finally accurately weigh the weight of the dark brown vein boletus polysaccharide nanosilver hydrogel after sufficient drying. Calculate the degradation rate of the dark brown vein boletus polysaccharide nanosilver hydrogel according to the following formula:
[0058] Degradation rate (%) = (M 后 -M 前 ) / M 前 ×100%
[0059] Where M 前 is the weight of the dark brown veined boletus polysaccharide nanosilver hydrogel after the first drying, M 后 is the weight of the Suillus edulis polysaccharide nanosilver hydrogel after swelling for 24 hours and then drying for 24 hours.
[0060] 4. Calculation of comprehensive score
[0061] In order to compare the overall effect of the dark brown veined boletus polysaccharide nanosilver hydrogel, it is necessary to comprehensively consider its water loss rate, swelling rate and degradation rate. This application uses a comprehensive score as an evaluation index, where the weight coefficient of the water loss rate is 0.2, the weight coefficient of the degradation rate is 0.2, and the weight coefficient of the swelling rate is 0.6. The data is normalized according to the formula:
[0062] Comprehensive score = (0.2×X+0.2×Y+0.6×Z)×100%
[0063] Note: X is water loss rate; Y is degradation rate; Z is swelling rate.
[0064] 2. Single factor test of dark brown veined boletus polysaccharide nanosilver hydrogel
[0065] 1 Reaction temperature
[0066] Take 30mL of dark brown stalked boletus polysaccharide nanosilver solution and add hydrogel raw materials at a mass fraction of 27%, that is, add 8.1g of hydrogel raw materials to 30mL of dark brown stalked boletus polysaccharide nanosilver solution. The mass ratio of polyvinyl alcohol, gelatin and carboxymethyl chitosan is 1:1:1. Dissolve 2.7g of polyvinyl alcohol at 90°C, then cool to 50°C, add 2.7g of gelatin, and continue to add 2.7g of carboxymethyl chitosan after it is dissolved. React at 30°C, 40°C, 50°C, 60°C, and 70°C for 30 minutes respectively to finally obtain PPP-AgNPs-xP-yG-zC hydrogel. The experiment was repeated 3 times, and the results are as follows Figure 1 shown.
[0067] Depend on Figure 1 It can be seen that with the increase of reaction temperature, the water loss rate of dark brown vein boletus polysaccharide nanosilver hydrogel gradually decreased, while the swelling rate, degradation rate and comprehensive score showed a trend of first increasing and then decreasing. Specifically, when the reaction temperature was 50℃, the swelling rate, degradation rate and comprehensive score of dark brown vein boletus polysaccharide nanosilver hydrogel reached the highest; while at 30℃, the water loss rate of dark brown vein boletus polysaccharide nanosilver hydrogel was the highest. Therefore, the optimal reaction temperature of dark brown vein boletus polysaccharide nanosilver hydrogel was determined to be 50℃ for response surface experiment.
[0068] 2. Reaction time
[0069] Take 30mL of dark brown boletus polysaccharide nanosilver solution, add the hydrogel raw material at a mass fraction of 27%, that is, add 8.1g of hydrogel raw material to 30mL of dark brown boletus polysaccharide nanosilver solution. The mass ratio of polyvinyl alcohol, gelatin and carboxymethyl chitosan is 1:1:1, that is, add 2.7g of polyvinyl alcohol, dissolve it at 90°C, then cool it to 50°C and add 2.7g of gelatin, and after it dissolves, continue to add 2.7g of carboxymethyl chitosan, and react at 50°C for 15min, 30min, 45min, 60min, and 90min to obtain PPP-AgNPs-xP-yG-zC hydrogel. The experiment was repeated 3 times, and the results are as follows Figure 2 shown.
[0070] Depend on Figure 2It can be seen that with the increase of reaction time, the water loss rate, swelling rate and comprehensive score of the dark brown veined boletus polysaccharide nanosilver hydrogel showed a trend of first decreasing, then increasing and then decreasing, while its degradation rate showed a trend of first increasing and then decreasing. When the reaction time was 60 minutes, the comprehensive score of the dark brown veined boletus polysaccharide nanosilver hydrogel showed an inflection point, so the reaction time of 45 minutes, 60 minutes and 90 minutes were selected for response surface experiment.
[0071] 3. Hydrogel raw material mass ratio
[0072] Take 30mL of dark brown vein boletus polysaccharide nanosilver solution and add hydrogel raw materials according to the mass fraction of 27%, that is, add 8.1g of hydrogel raw materials to 30mL of dark brown vein boletus polysaccharide nanosilver solution. Then add a certain amount of polyvinyl alcohol (PVA), dissolve it at 90℃, then cool it to 50℃, add a certain amount of gelatin (Gelatin), and continue to add a certain amount of carboxymethyl chitosan (CMCS) after the gelatin is dissolved. After reacting at 50℃ for 30min, PPP-AgNPs-xP-yG-zC gel is obtained. The ratios of m(PVA):m(Gelatin):m(CMCS) were investigated, and X1=1:2:2 (masses were 1.62g, 3.24g,
[0073] 3.24g), X2=2:1:2 (the masses are 3.24g, 1.62g, and 3.24g respectively), X3=2:2:1 (the masses are 3.24g, 3.24g, and 1.62g respectively), and X4=1:1:1 (the masses are 2.7g, 2.7g, and 2.7g respectively).
[0074] The experiment was repeated 3 times and the results were as follows Figure 3 shown.
[0075] Depend on Figure 3 It can be seen that when the raw material mass ratio is 1:2:2, the swelling rate and comprehensive score of the dark brown vein boletus polysaccharide nanosilver hydrogel are the highest; when the raw material mass ratio is 2:2:1, the swelling rate and comprehensive score of the dark brown vein boletus polysaccharide nanosilver hydrogel are the lowest; when the raw material mass ratio is 2:1:2, the degradation rate of the dark brown vein boletus polysaccharide nanosilver hydrogel is the highest; when the raw material mass ratio is 1:1:1, the water loss rate of the dark brown vein boletus polysaccharide nanosilver hydrogel is the highest. There is an inflection point when the raw material mass ratio is 2:2:1. Therefore, the raw material mass ratios of 2:1:2, 2:2:1, and 1:1:1 were selected for the response surface optimization experiment.
[0076] 4. Mass fraction of hydrogel raw materials
[0077] Take 30mL of dark brown veined boletus polysaccharide nanosilver solution, the ratio of m(PVA)∶m(Gelatin)∶m(CMCS) is 1:1:1. The total mass fractions of the raw materials investigated were 17%, 22%, 27%, 32%, and 37%, respectively. Specifically, the corresponding amount of polyvinyl alcohol was added, which were 1.7g, 2.2g, 2.7g, 3.2g, and 3.7g, respectively, and dissolved at 90°C, then cooled to 50°C, and then the corresponding mass of gelatin was added, which were 1.7g, 2.2g, 2.7g, 3.2g, and 3.7g, respectively. After dissolution, the corresponding mass of carboxymethyl chitosan was continued to be added, which were 1.7g, 2.2g, 2.7g, 3.2g, and 3.7g, respectively. React at 50°C for 30 minutes to obtain PPP-AgNPs-xP-yG-zC hydrogel. The experiment was repeated 3 times, and the results are as follows Figure 4 shown.
[0078] Depend on Figure 4 It can be seen that with the increase of the mass fraction of the hydrogel raw material, the water loss rate, swelling rate, degradation rate and comprehensive score of the dark brown veined boletus polysaccharide nanosilver hydrogel all showed a downward trend. When the mass fraction of the hydrogel raw material of the dark brown veined boletus polysaccharide nanosilver hydrogel reached 32%, its comprehensive score dropped sharply. Therefore, we selected the mass fractions of the hydrogel raw material of 27%, 32% and 37% for the response surface experiment.
[0079] 5. Response surface optimization experiment
[0080] Based on the results of the single factor experiment, the Box-Behnken design experiment in the software Design-Expert13 was used to investigate the comprehensive effects of reaction time, reaction temperature, raw material mass ratio and hydrogel raw material mass fraction on the swelling, water loss and degradation of Boletus edulis polysaccharide nanosilver hydrogel with the comprehensive score as the response value. A response surface experiment design was carried out. The specific factor levels are shown in Table 1.
[0081] Table 1 Independent variable factors and level coding of Box-Behnken test of Boletus edulis polysaccharide nanosilver hydrogel
[0082]
[0083] According to the design factors in Table 1, the Box-Behnken experimental design in the software Design-Expert13 was used to obtain the optimal experimental conditions. The response surface test results are shown in Table 2.
[0084] Table 2 Response surface test results of dark brown veined boletus polysaccharide nanosilver hydrogel
[0085]
[0086]
[0087] The software was used to perform a multivariate regression fit on the data in Table 2, and the obtained quadratic multinomial regression model equation was: Y(%) = -409.2 + 11.34A + 29.77B - 21.05C - 0.037AB + 0.55AC + 0.35BC - 0.114A 2 -0.607B 2 -0.675C 2 The results of variance analysis of the regression model are shown in Table 3.
[0088] Table 3 Analysis of variance of regression model for response surface test of Boletus edulis polysaccharide nanosilver hydrogel
[0089] Sources of variance sum of squares Degrees of Freedom Mean Square F-number P-value Significance Regression Model 10253.74 9 1139.30 3.74 0.0481 * A 40.50 1 40.50 0.1328 0.7263 - B 2812.50 1 2812.50 9.22 0.0189 - C 3120.50 1 3120.50 10.23 0.0151 - AB 30.25 1 30.25 0.0992 0.7620 - AC 272.25 1 272.25 0.8925 0.3762 - BC 12.25 1 12.25 0.0402 0.8469 - <![CDATA[A 2 ]]> 2775.60 1 2775.60 9.10 0.0195 - B2 969.60 1 969.60 3.18 0.1178 - C2 1.92 1 1.92 0.0063 0.9390 - Residual 2135.20 7 305.03 - - - Lack of Fit 556.00 3 185.33 0.4694 0.7197 NS Pure Error 1579.20 4 394.80 - - - Total deviation 12388.94 16 - - - -
[0090] Note: *P<0.05 indicates a significant effect, and NS (P>0.05) indicates no significance.
[0091] The response surface diagram of the interactive effects of various factors of dark brown veined boletus polysaccharide nanosilver hydrogel on the comprehensive score is shown in Figure 5 As shown. The more convex the graph is, the greater the influence of these factors on the water loss, degradation and swelling of the dark brown vein boletus polysaccharide nanosilver hydrogel, indicating that the experiment is significant. The surface plot of the interaction term between the mass fraction of the hydrogel raw material and the mass ratio of the hydrogel raw material shows a steep slope, and the contour lines are densely arranged or elliptical, indicating that the interaction has a significant effect on the water loss, degradation and swelling of the dark brown vein boletus polysaccharide nanosilver hydrogel. According to the response surface test, the optimal process conditions for preparing the dark brown vein boletus polysaccharide nanosilver hydrogel are reaction time 90min, hydrogel raw material mass fraction 27%, and hydrogel raw material mass ratio 1:1:1. The experiment was carried out on the basis of the optimal reaction temperature of 50℃ obtained by the single factor experiment, and the results showed that the comprehensive score of the dark brown vein boletus polysaccharide nanosilver hydrogel was 361%. The verification experiment was carried out on the group with the highest comprehensive score, that is, group 14, and the comprehensive score obtained was 345%, which was close to the initial result, proving that the results are reliable. Therefore, the optimal process conditions for the preparation of the Boletus edulis polysaccharide nanosilver hydrogel are reaction temperature of 50°C, reaction time of 90 min, hydrogel raw material mass fraction of 27%, and raw material mass ratio of 1:1:1. Under these conditions, the comprehensive score of the Boletus edulis polysaccharide nanosilver hydrogel can reach 361%.
[0092] Example 3
[0093] This example provides the performance test and structural characterization of Boletus edulis polysaccharide nanosilver hydrogel.
[0094] 1. Performance test of dark brown veined boletus polysaccharide nanosilver hydrogel
[0095] The prepared dark brown veined boletus polysaccharide nanosilver hydrogel was spread on the palm, plastic and glove surfaces to observe its adhesion state and ductility. Figure 6 .
[0096] like Figure 6 As shown, Figure a shows the state of the dark brown veined boletus polysaccharide nanosilver hydrogel adhering to the back of the hand; Figure b shows its state of adhering to plastic; Figure c shows its state of adhering to gloves. The dark brown veined boletus polysaccharide nanosilver hydrogel can achieve good adhesion effects on the surfaces of these three objects, and can be easily spread on the surface of the object, indicating that it has good adhesion and ductility.
[0097] 2. Structural Characterization of Boletus edulis Polysaccharide Nanosilver Hydrogel
[0098] 2.1 Fourier transform infrared spectroscopy
[0099] Take 2 mg of the dark brown veined boletus polysaccharide nanosilver hydrogel prepared in Example 1 and 100 mg of potassium bromide (KBr) powder, grind them evenly, put them in an oven to dry the moisture, and press them into transparent sheets of uniform thickness. -1 Infrared spectrum scanning is performed within the range.
[0100] like Figure 7 As shown, the Fourier transform infrared spectrometer (Thermo Fisher Scientific Co., Ltd.) was used at 4000-400 cm -1 The chemical structures of dark brown veined boletus polysaccharide nanosilver hydrogel, polyvinyl alcohol, gelatin and carboxymethyl chitosan were analyzed within a certain range. The absorption peaks of carboxymethyl chitosan are located at 3430 cm -1 、2880cm -1 and 1610cm -1 , corresponding to the symmetrical vibration of -OH and -NH, the stretching vibration of -CH, the stretching vibration of -CN or the symmetrical and asymmetrical vibration of -COO. Polyvinyl alcohol at 3420cm -1 、621cm -1 and 1090cm -1 The absorption peaks at 1650 cm-1 and 1650 cm-2 are attributed to the vibration of -OH, the bending vibration of -OH and the vibration of CO. -1 、1550cm -1 and 3360cm -1 , corresponding to the stretching vibration of C=O, the stretching vibration of CN and the angular vibration of NH. In the infrared spectrum of the dark brown veined boletus polysaccharide nanosilver hydrogel, the characteristic peaks of all the above characteristic functional groups were detected, indicating that the reactants were successfully introduced and the dark brown veined boletus polysaccharide nanosilver hydrogel was formed.
[0101] 2.2 Scanning electron microscopy
[0102] After the dark brown veined boletus polysaccharide nanosilver hydrogel prepared in Example 1 was fully dried and ground, an appropriate amount was placed on a sample stage with a conductive glue attached, and observed using a scanning electron microscope (ZEISS Sigma500 emission scanning electron microscope, Zeiss, Germany) at an accelerating voltage of 15 kV.
[0103] As a skin wound dressing, the dark brown veined boletus polysaccharide nanosilver hydrogel should have a structure that allows water and drugs to pass through. Figure 8 As shown in the figure, the microstructure of the dark brown veined boletus polysaccharide nanosilver hydrogel was observed by scanning electron microscopy, and it can be seen that its surface is relatively smooth and dense, but the interior is porous and has a high cross-linking density. These structural features are conducive to oxygen supply, drug release and exudate absorption.
[0104] Example 4
[0105] This example provides the antibacterial effect of Boletus edulis polysaccharide nanosilver hydrogel and evaluates its in vitro antibacterial activity.
[0106] 1. Culture medium preparation
[0107] Preparation of LB solid culture medium: Weigh 4.00g of LB broth and 4.00g of agar into a conical flask, add 200mL of deionized water, stir evenly, and obtain a culture medium with 2% (w / v) agar. Seal the conical flask with a filter membrane and sterilize it at 121℃ for 20min. Pour the sterilized culture medium into a plate, pour about 10mL of culture medium into each plate, cool it to room temperature to form a solid culture medium plate, and finally put it into a 4℃ refrigerator for use.
[0108] Preparation of LB liquid culture medium: Weigh 4.00g of LB broth into a conical flask, add 200mL of deionized water, mix well, and obtain a 2% (w / v) LB broth culture medium. Seal the conical flask with a filter membrane, sterilize at 121℃ and high pressure for 20min, and finally put it in a 4℃ refrigerator for use.
[0109] 2 Bacterial culture
[0110] Take out the frozen Staphylococcus aureus and Escherichia coli from the -80℃ refrigerator, put them in a 37℃ water bath and shake them quickly until the bacteria are completely thawed. Then, take out 500μL of bacterial solution each, transfer it to a centrifuge tube containing 20mL of liquid culture medium, and mix it thoroughly by blowing. Then, place it in a desktop constant temperature oscillator (37℃, 220r / min) and culture it overnight until the bacteria grow to the logarithmic growth phase. Finally, use a spectrophotometer to adjust the absorbance of the bacteria at 600nm to 0.6-0.8.
[0111] 3 Inhibition Zone
[0112] Take 50 μL of bacterial solution in the middle of the logarithmic growth phase and evenly spread it on the solid culture medium plate. Use the spreading rod to make circular motions to fully cover the solid culture medium with the bacterial solution. Then, take out the sterile drug-sensitive paper soaked in PBS (Group A), the drug-sensitive paper soaked in the dark brown vein boletus polysaccharide nanosilver aqueous solution (Group B), the dark brown vein boletus polysaccharide nanosilver hydrogel (Group C) and the blank hydrogel (Group D), place them on the solid culture plate coated with bacteria on the surface, and incubate them in a 37°C incubator for 24 hours. Observe whether an inhibition zone is formed around the hydrogel, and measure the diameter of the inhibition zone. The inhibition zone results of Escherichia coli are as follows: Fig. 9 The inhibition zone results of Staphylococcus aureus are shown in Fig.10 shown.
[0113] Depend on Fig. 9 and Fig.10 It can be seen that there are transparent zones around paper pieces b and c, indicating that the dark brown-veined boletus polysaccharide nanosilver solution and its hydrogel preparation have inhibitory effects on Escherichia coli and Staphylococcus aureus, and the inhibitory effect on Staphylococcus aureus is stronger.
[0114] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred embodiments of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.
Claims
1. A dark brown veined boletus polysaccharide nanosilver hydrogel, characterized in that: The invention comprises dark brown stalked boletus polysaccharide, silver nitrate and hydrogel raw materials, and the proportion is 0.2 mg / mL: 0.004 mmol / mL: 0.17-0.32 g / mL.
2. The dark brown veined boletus polysaccharide nanosilver hydrogel according to claim 1, characterized in that: The hydrogel raw materials include polyvinyl alcohol, gelatin and carboxymethyl chitosan in a mass ratio of 1:1-2:1-2.
3. The dark brown veined boletus polysaccharide nanosilver hydrogel according to claim 1, characterized in that: The ratio of dark brown veined boletus polysaccharide, silver nitrate and hydrogel raw material is 0.2 mg / mL: 0.004 mmol / mL: 0.27 g / mL; The mass ratio of polyvinyl alcohol, gelatin and carboxymethyl chitosan is 1:1:
1.
4. The dark brown veined boletus polysaccharide nanosilver hydrogel according to claim 1, characterized in that: Suillus edulis polysaccharide nanosilver hydrogel can inhibit the growth of Escherichia coli and Staphylococcus aureus.
5. A method for preparing a dark brown veined boletus polysaccharide nanosilver hydrogel, characterized in that: include: Adding a dark brown veined boletus polysaccharide solution into a silver nitrate solution to obtain a dark brown veined boletus polysaccharide nanosilver solution; Add polyvinyl alcohol to the dark brown vein boletus polysaccharide nanosilver solution, dissolve it, cool it down, add gelatin, add carboxymethyl chitosan after it dissolves, react at 30-60°C for 15-60min, and prepare the dark brown vein boletus polysaccharide nanosilver hydrogel.
6. The preparation method according to claim 5, characterized in that: The raw materials for preparing the dark brown stalked boletus polysaccharide nanosilver hydrogel include dark brown stalked boletus polysaccharide, silver nitrate and hydrogel raw materials, and the ratio is 0.2 mg / mL: 0.004 mmol / L: 0.17-0.32 g / mL.
7. The preparation method according to claim 5, characterized in that: After adding polyvinyl alcohol, gelatin and carboxymethyl chitosan into the dark brown vein boletus polysaccharide nanosilver solution and reacting at 50℃ for 30min, dark brown vein boletus polysaccharide nanosilver hydrogel was prepared.
8. Use of the Boletus edulis polysaccharide nanosilver hydrogel according to any one of claims 1 to 7 in the preparation of a preparation for inhibiting or killing Escherichia coli and / or Staphylococcus aureus.
9. A medical antibacterial dressing, characterized in that: The medical antibacterial dressing comprises the dark brown veined boletus polysaccharide nanosilver hydrogel of claim 1.
10. Application of Boletus edulis polysaccharide nanosilver hydrogel in the preparation of antibacterial preparations.